Tinjauan Perlindungan Hukum Konsumen Rokok Tanpa Label Peringatan Kesehatan Berupa Gambar Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen (Putusan Nomor 410/Pid.Sus/2020/PN Btm) - Angela Devina; Vera W. S. Soemarwi (Fakultas Hukum Universitas Tarumanagara, 2022)
In Indonesia, many business actors do commerce of various brands of cigarettes legally and illegally.Legal means that the cigarette has a distribution permit and has a health warning label in the form ofan image on the package and illegal is a cigarette that does not have a health warning label in theform of an image on the package. Where cigarettes without a health warning label in the form ofimages on the packaging are very detrimental to smokers as cigarette consumers. Various ef ortshave been made by the government such as issuing Government Regulation No. 109 of 2012concerning the Safety of Materials Containing Addictive Substances in the Form of Tobacco Productsfor Health, the Decree of the Head of the Food and Drug Supervisory Agency of the Republic ofIndonesia (BPOM RI) is regulated on Procedures for Supervision of Circulation of CigaretteProducts and Advertising. Regarding health warnings in the form of images and writings that haveone meaning printed together with product packaging, it is very clear that it is the obligation ofbusiness actors as stated in Article 14 of Government Regulation No. 109 of 2012 and also regulatedin Article 4 of Law Number 8 of 1999 concerning Consumer Protection and Article 7 of Law Number8 of 1999 concerning Consumer Protection (hereinafter referred to as UUPK).